2015
DOI: 10.1016/j.cherd.2015.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Physical absorption of volatile organic compounds by spraying emulsion in a spray tower: Experiments and modelling

Abstract: Absorption Volatile organic compound (VOC) Emulsion Gas-liquid Mass transfer coefficient a b s t r a c t This study outlines a volatile organic compounds (VOCs) removal spray tower consisting of an empty cylindrical vessel and nozzles spraying an oil/water emulsion into the vessel. Spraying an emulsion into a spray tower absorbs both lipophilic and hydrophilic compounds, facilitates oil transport, improves the interfacial area (oil coats water droplets) and increases the turbulent flow regime enhancing mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Because toluene is not absorbed in water (Tatin et al, 2015), we had to consider only the oil interfacial area involved in the mass transfer operation. We introduced an oil cover ratio (D which is directly linked to the oil:water emulsion ratio if we assume an isotropic emulsion.…”
Section: Interfacial Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Because toluene is not absorbed in water (Tatin et al, 2015), we had to consider only the oil interfacial area involved in the mass transfer operation. We introduced an oil cover ratio (D which is directly linked to the oil:water emulsion ratio if we assume an isotropic emulsion.…”
Section: Interfacial Areamentioning
confidence: 99%
“…Other works have been published on the absorption method using a siloxane/water emulsion (Dumont et al, 2012), or silicone oil/water emulsion (Tatin et al, 2015). Most of these studies operated in a semi-batch system using recirculation of the emulsion without any regeneration of the VOC-saturated oil.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Traditional VOC retrieval procedures are expensive and dependent on several variables, such as temperature, gas flow rate and pollutant concentration (Tatin et al, 2015). Conventional VOC removal requires resources and materials not only to maintain a high temperature, high pressure, and sometimes adiabatic system but when replacing and discarding spent catalysts.…”
Section: Technical Discussion and Methodsmentioning
confidence: 99%
“…Alternatively, Tatin et al (2015) analyzed the effectiveness of using a water/silicone oil emulsion to capture VOCs in spray towers. In this study the researchers found that the emulsion was up to 90% effective at VOC removal.…”
Section: Technical Discussion and Methodsmentioning
confidence: 99%